Underage cigarette smoking and the laws in Malaysia / Nik Noor Azan Nik Ismail and Mohammad Supian Mohd Yaacob - Nik Ismail, Nik Noor Azan; Mohd Yaacob, Mohammad Supian (2011)
Cigarette contains nicotine, a highly addictive chemical that is deriving from tobacco leaves. Once someone is hooked to the habit, it's difficult to stop. Majority of the smokers initiated smoking during their teens age. In fact, the age of people who started smoking is getting younger. This study examines the laws and regulations that tackle the issue of underage cigarette smoking and identify the relevant enforcement agencies and the effectiveness of their actions. The qualitative method of study is used for this research. The Control of Tobacco Product Regulation is the main statute that governs the issue of underage cigarette smoking issue. There are also some other laws that may have connection with the tobacco control, such as the Customs Act 1967 and the Excise Act 1976. These two Acts cover the taxation, production, manufacturing and distribution of the tobacco product which may indirectly impact the tobacco consumption by the underage. The Education Act 1996 and regulations play an important role in combating the tobacco epidemic among the school children. Nevertheless, the weak punishment and the lack of enforcement activities do not help to curb this problem. Furthermore, the commitment of the government in tackling the issue seems to be insufficient. More efforts are needed to educate the society and stricter policy should be applied to ensure the underage are fully protected from the dangers of cigarette smoking.